Gambaran Kepadatan Dan Identifikasi Lalat (Diptera) Di Pasar Waiheru Perumnas Kecamatan Baguala Kota Ambon - Farha Assagaf; Arfan Ohorella; Amry Jusuf (Universitas Muhamadiyah Manado, 2024)
Flies are vectors for disease transmission, especially mechanically and through their vomit and feces. Items, especially food, are usually contaminated by human feces, rubbish, the saliva of sick people, scars from animal carcasses and other things that are covered in flies. Flies can throw feces on food so that the food becomes contaminated with fly eggs and larvae. Disruption of comfort, eyesore, itching of the skin, causing discomfort, decreased appetite. To determine the density and identification of flies in the Waiheru Perumnas market, Baguala District, Ambon City. Type of descriptive research that describes a condition based on observation and examination of the Ambon Environmental Health Engineering Center (BTKL) Laboratory. The aim of descriptive research is to describe the density and identification of flies in the Waiheru Perumnas market, Baguala District, Ambon City. Measuring the density of flies in the Waiheru Perumnas market, Baguala District, Ambon City is based on 3 points, 10 measurements at each point in the morning, at the first point (los fish) amounted to 87 flies, at point II (vegetable stall there were 55 flies and at point III (fruit stall) there were 45 flies. Identification of fly types resulted in 3 types of flies identified, namely Musca Domestica (house fly), Cliphora Sp (green flies) and Sarcophaga (meat flies). The density of flies in the Waiheru Perumnas market, Baguala District, Ambon City, based on the installation of fly grills based on the 10 highest points, was 187 flies and at the 5 highest points was 134 flies with 23 flies caught in the fly trap. From the results obtained, it can be seen that the density of flies is very high so it is necessary to deal with fly breeding sites and fly control measures.